Solvation of atomic fluorine in bulk superfluid 4He - Eloranta, J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Bosonic density functional theory calculations were carried out for fluorine atom solvated in superfluid 4He with an emphasis on the formation of dimeric species in the liquid. Atomic fluorine displays a relatively strong binding and anisotropic interaction with helium and hence the resulting solvation structure contains highly localized liquid helium layers. These solvent layers modify the gas phase dimer potentials by inclusion of a recombination barrier, which provides stabilization for the solvated fluorine atoms. At 0 K and saturated vapor pressure, the recombination barrier for the formation of molecular fluorine ( 2Σg+) in superfluid helium is predicted to be 26.8 K. At temperatures below 1 K, this barrier prevents the F–F recombination as all the other electronic states correlating with the ground state atoms are essentially repulsive. It is concluded that it should be possible to stabilize fluorine atoms in superfluid helium below 1 K temperatures.